Development of herbal candy using ginger essential oil - Shukla, Preeti; Bhise, Suresh; Gaikwad, Balaji (Journal of Postharvest Technology, 2018)
Herbs and spices play an important role for medicinal purposes. Ginger and tulsi are herbs being used in Indian system of medicine during  cold and cough. Candy is a fast and effective delivery system for medications. An investigation was planned to prepare herbal candy by  standard method and used ginger oil to enhance medicinal value in sugar based candy. Hard boiled sugar candy was developed by optimization of citric acid and ginger oil. The results of physio-chemical and sensory characteristics of herbal candy revealed that sugar candy  prepared using sugar and corn syrup (70:30) and 0.5 per cent citric acid produced candy with higher overall acceptability score (7.7) The  moisture, reducing sugar, total sugar, titratable acidity of herbal candy were 1.85, 60.7, 92.85 and 0.81 per cent respectively. Total soluble  solids, hardness and pH of herbal candy using ginger oil were 93oBrix, 595.083 N and 3.86, respectively. The ginger oil concentration at 2.5  per cent produced maximum overall acceptability score (7.05) with less score for colour, texture and mouth feel as compared to herbal candy  produced at 2.0 per cent ginger oil. The temperature at 145ºC produced best consistency, moudlability, thread forming ability, brittleness along  with desirable taste and colour. The herbal candy prepared at 145ºC had best hardness with desirable sensory characteristics, maximum  overall acceptability score (7.35) with less score for colour and taste as compared to herbal candy produced at 155ºC.
Keywords: herbal candy,; ginger candy; hard boiled candy,; ginger oil